Resistance of lesbian, transgender, bisexual, gay and intersex workers in society and at work (Research, Society and Development, 2020)
This article aims to analyze the resistance of lesbian, transgender, intersex bisexual and intersex in the face of homophobia practices and heteronormative violence in the context of organizations, work and society, as well as the possibilities of resistance around a critical and reflective posture on dominant patterns. and hegemonic in sexuality. To this end, we discuss homophobia, heteronormativity and violence at work. Thus, we conducted a qualitative research using oral history focusing on their professional trajectories and analyzed the data through qualitative content analysis by the categories of "resisting violence" and "overcoming and critical analysis around violence". There are many ways to deal with prejudice in the workplace from the subtlest to the most explicit. In general, it is noteworthy that overcoming violence may be related to a critical and reflexive analysis around the dominant and heteronormative point of view, the full acceptance of their sexuality, the questioning of violence, the search for information and of enlightenment, and with better self-esteem.